Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T15:40:15+01:00
A) 2x+1-3x+4+3x=2x+5
b) 5a+6a-2-12a+9-2a=-3a+7
c) 0,2y-0,1-2,5+7,5y-2,5=7,7y-5,1
d) 10x-15y+12x-4y-6x+7y=16x-12y
2010-02-22T15:41:59+01:00
A) 2x+1-3x+4+3x
wyrazy podobne skreślamy, czyli 3x reszte dodajemy
= 2x+5

b) 5a+6a-2-12a+9-2a
sumujemy wszystkie a, i to co jest bez literki
= -3a+7

c) 0,2y-0,1-2,5+7,5y-2,5
sumujemy y
= 7,7y - 5,1

d) 10x-15y+12x-4y-6x+7y = 16x - 12y
2010-02-22T15:45:18+01:00
A)
2x+1-3x+4+3x = 2x - 3x+ 3x +1+4=2x+5
b)
5a+6a-2-12a+9-2a=5a+6a-12a-2a-2+9=-3 +7
c)
0,2y-0,1-2,5+7,5y-2,5=0,2y+7,5y -0,1 -2,5+7-2,5=7,7y -5,1
d)
10x-15y+12x-4y-6x+7y= 10x +12x-6x-15y-4y+7y=16x -12y